2019
DOI: 10.1021/acs.jpcb.8b11970
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Dependent Signaling in Simulations of a Revised Model of Cystic Fibrosis Transmembrane Conductance Regulator (CFTR)

Abstract: Cystic fibrosis transmembrane conductance regulator (CFTR) is a member of the ATP-binding cassette (ABC) transporter superfamily that has uniquely evolved to function as a chloride channel. It binds and hydrolyzes ATP at its nucleotide binding domains to form a pore providing a diffusive pathway within its transmembrane domains. CFTR is the only known protein from the ABC superfamily with channel activity, and its dysfunction causes the disease cystic fibrosis. While much is known about the functional aspects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…In a recent study of Cryo-EM structure analysis, Fay et al (18a) observed that the dephosphorylated R domain of chicken CFTR possibly interacts with CL1, supporting the idea that the R domain could regulate the interaction between the x-loop and CL1 by limiting the motion of CL1 under the condition of dephosphorylation. It is interesting to note that Strickland et al (38) recently reported that charge interaction between E543 in the x-loop of NBD1 and K968 in CL3 promotes channel phosphorylation by showing fast time course of activation, supporting the idea that interaction between the x-loop and CLs is important for signal transmission generated by ATP-dependent NBD dimerization and also implying a functional asymmetry between the two x-loops and their counterpart of CLs. Taken together, our present data provide new evidence that phosphorylation regulates CFTR channel activity independently of ATP-dependent NBD dimerization and support the idea that the R domain has divided labors that allosterically promote CFTR channel activity by targeting different gating elements (46), including interaction between the x-loop and CLs that is involved in conformational change requisite for CFTR channel opening.…”
Section: L781mentioning
confidence: 71%
“…In a recent study of Cryo-EM structure analysis, Fay et al (18a) observed that the dephosphorylated R domain of chicken CFTR possibly interacts with CL1, supporting the idea that the R domain could regulate the interaction between the x-loop and CL1 by limiting the motion of CL1 under the condition of dephosphorylation. It is interesting to note that Strickland et al (38) recently reported that charge interaction between E543 in the x-loop of NBD1 and K968 in CL3 promotes channel phosphorylation by showing fast time course of activation, supporting the idea that interaction between the x-loop and CLs is important for signal transmission generated by ATP-dependent NBD dimerization and also implying a functional asymmetry between the two x-loops and their counterpart of CLs. Taken together, our present data provide new evidence that phosphorylation regulates CFTR channel activity independently of ATP-dependent NBD dimerization and support the idea that the R domain has divided labors that allosterically promote CFTR channel activity by targeting different gating elements (46), including interaction between the x-loop and CLs that is involved in conformational change requisite for CFTR channel opening.…”
Section: L781mentioning
confidence: 71%
“…In addition, several homology models of CFTR were developed using structures of related ABC transporters as a template. These studies contributed to the understanding of the molecular interface encompassing the most common CF-causing mutation (ΔF508; Mornon et al, 2008 ; Serohijos et al, 2008 ), as well as several details relating to the conformational transitions underlying CFTR gating ( Corradi et al, 2015 ; Dalton et al, 2012 ; Furukawa-Hagiya et al, 2013 ; Mornon et al, 2015 ; Mornon et al, 2009 ; Rahman et al, 2013 ; Strickland et al, 2019 ). However, the disparity between the wide variety of substrates of nonchannel ABC transporters and the chloride channel function of CFTR resulted in intrinsically limited confidence in these homology models, at least with respect to the TMDs.…”
Section: Molecular Evolution Of Channel Functionmentioning
confidence: 99%
“…9 A depicts a simplified model of these sites, wherein each ABS is shown to consist of the so-termed Walker A, Walker B, and H loop regions from one NBD and the ABC signature and D loops from the other NBD. ATP binding to an ABS promotes NBD dimerization, which “powers” active transport by driving conformational changes in the TMDs ( Rahman et al, 2013 ; Strickland et al, 2019 ); in ABC exporters, this flips the TMD conformation from inward to outward facing ( Rees et al, 2009 ). ATP hydrolysis at these sites leads to dissociation of the NBD dimer, which allows the readoption of the inward-facing conformation to bind new intracellular substrates, although there is significant disagreement regarding the degree of dissociation undergone at the NBDs to accomplish this ( George and Jones, 2012 ; Hohl et al, 2014 ; Puljung, 2015 ; Zoghbi et al, 2012 ).…”
Section: Molecular Evolution Of Channel Functionmentioning
confidence: 99%
See 2 more Smart Citations